2006
DOI: 10.1002/jmri.20600
|View full text |Cite
|
Sign up to set email alerts
|

MR‐guided breast biopsy using an active marker: A phantom study

Abstract: Purpose:To evaluate the advantages of using an active marker (active micro coil) for MR-guided breast biopsy procedures. Materials and Methods:An add-on breast biopsy guidance device used with a standard breast coil was equipped with an active marker. The marker's position was determined with a dedicated MRI sequence. In combination with custom software, the biopsy planning process was reduced basically to defining the target in the diagnostic MR images. Automatic control scans verified the settings of the bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…Also, they require manual retrieval of the passive markers in the image data and calculation of the needle position. The planning, adjustment, and starting of MR scans typically need to be performed manually [42]. The use of RF coils [26] and rapid MR-tracking [22] techniques are also limited by the need for continual use of the scanner in order to image and visualize the devices.…”
Section: Introductionmentioning
confidence: 99%
“…Also, they require manual retrieval of the passive markers in the image data and calculation of the needle position. The planning, adjustment, and starting of MR scans typically need to be performed manually [42]. The use of RF coils [26] and rapid MR-tracking [22] techniques are also limited by the need for continual use of the scanner in order to image and visualize the devices.…”
Section: Introductionmentioning
confidence: 99%
“…With the emerging role of breast MRI, several studies reported on techniques to localize breast tumors under realtime MRI guidance. [12][13][14][15][16][17][18][19][20][21]41,53 Although the results are promising, the procedures, especially the ones performed in closed-bore magnets, require extended time slots on the MRI unit which may press heavily on the MRI capacity of many radiology clinics. Moreover, specific MR-compatible instruments are required and multiple administrations of contrast agent may be necessary because the optimal window of enhancement in breast tumors is typically limited to the first 10 min.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies demonstrated the feasibility of MRIguided localization and bracketing of breast cancer. [12][13][14][15][16][17][18][19] Initial experiences with wire localization using an open-bore system were promising, but required procedure times of up to 36 min at the MRI unit. 20 MRI-guided localization of tumor extent ͑using, e.g., bracketing wires͒ has been reported to aid in complete tumor excision.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 1 shows a lateral view of a patient prepared for stereotactic breast biopsy in a vertical open 0.5T scanner. The attachment of an automatically detectable MR marker in the stereotactic frame can facilitate the adjustment of the guiding device (12).…”
Section: Principles Of Navigationmentioning
confidence: 99%
“…These MR reference markers may be subdivided into active and passive markers (110). Active markers are small radiofrequency (RF) coils that are connected to the regular receiver channels of the MR system (12, 96, 111–113). Therefore, these markers are independently selectable by the scanner software and can be rapidly and automatically localized using a 1D projection technique (111).…”
Section: Pulse Sequences and Related Mri Techniquesmentioning
confidence: 99%